Greenland, muskoxen on Ymer Island, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
Fig. 14 - Shores of the large lake (Noa Lake) in the western part of Ymer Island in the depression leading from the head of Dusen Fiord to Franz Josef Fiord. Muskox appearing on the slope in the foreground. This part of Ymer Island supports an abundant plant and animal life. July 26, 1931. (Caption taken from Boyd, L. A. (1932). Fiords of East Greenland: A Photographic Reconnaissance throughout the Franz Josef and King Oscar Flords. Geographical Review, 22(4), 539.) Fiord region of East Greenland Boyd, L. A. (1932). Fiords of East Greenland: A Photographic Reconnaissance throughout the Franz Josef and King Oscar Flords. Geographical Review, 22(4), 529-561.